Home treatment for acute mental healthcare: randomised controlled trial. (June 2020) - Stulz, Niklaus; Wyder, Lea; Maeck, Lienhard; Hilpert, Matthias; Lerzer, Helmut; Zander, Eduard; Kawohl, Wolfram; grosse Holtforth, Martin; Schnyder, Ulrich; Hepp, Urs
Abstract : Background: Home treatment has been proposed as an alternative to acute in-patient care for mentally ill patients. However, there is only moderate evidence in support of home treatment. Aims: To test whether and to what degree home treatment services would enable a reduction (substitution) of hospital use. Method: A total of 707 consecutively admitted adult patients with a broad spectrum of mental disorders (ICD-10: F2–F6, F8–F9, Z) experiencing crises that necessitated immediate admission to hospital, were randomly allocated to either a service model including a home treatment alternative to hospital care (experimental group) or a conventional service model that lacked a home treatment alternative to in-patient care (control group) (trial registration at ClinicalTrials.gov: NCT02322437). Results: The mean number of hospital days per patient within 24 months after the index crisis necessitating hospital admission (primary outcome) was reduced by 30.4% (mean 41.3 v. 59.3, P <0.001) when a home treatment team was available (intention-to-treat analysis). Regarding secondary outcomes, average overall treatment duration (hospital days + home treatment days) per patient (mean 50.4 v. 59.3, P = 0.969) and mean number of hospital admissions per patient (mean 1.86 v. 1.93, P = 0.885) did not differ statistically significantly between the experimental and control groups within 24 months after the index crisis. There were no significant between-group differences regarding clinical and social outcomes (Health of the Nation Outcome Scales: mean 9.9 v. 9.7, P = 0.652) or patient satisfaction with care (Perception of Care questionnaire: mean 0.78 v. 0.80, P = 0.242). Conclusions: Home treatment services can reduce hospital use among severely ill patients in acute crises and seem to result in comparable clinical/social outcomes and patient satisfaction as standard in-patient care.